Safeguarding the process of drug administration with an emphasis on electronic support tools - Seidling, Hanna; Lampert, Anette; Lohmann, Kristina; Schiele, Julia T.; Send, Alexander Francesco Josef; Witticke, Diana; Haefeli, Walter E. (British journal of clinical pharmacology, 2013)
Aims The aim of this work is to understand the process of drug administration and identify points in the workflow that resulted in interventions by clinical information systems in order to improve patient safety. Methods To identify a generic way to structure the drug administration process we performed peer-group discussions and supplemented these discussions with a literature search for studies reporting errors in drug administration and strategies for their prevention. Results We concluded that the drug administration process might consist of up to 11 sub-steps, which can be grouped into the four sub-processes of preparation, personalization, application and follow-up. Errors in drug handling and administration are diverse and frequent and in many cases not caused by the patient him/herself, but by family members or nurses. Accordingly, different prevention strategies have been set in place with relatively few approaches involving e-health technology. Conclusions A generic structuring of the administration process and particular error-prone sub-steps may facilitate the allocation of prevention strategies and help to identify research gaps.